Reconstructing Digital Uzlah as an Intrapersonal Communication Strategy: An Islamic Ethical Response to the Pathology of Hyperconnectivity - Ahmad Sofian; Hasan Sazali; Muhammad Randicha Hamandia; Zhila Jannati (Indonesian Journal Publisher, 2026)
This article examines digital uzlah as an Islamic communication ethic for responding to hyperconnectivity, algorithmic distraction, and the weakening of intrapersonal communication in contemporary society. Using qualitative library research, the study analyzes classical Islamic ethical thought, communication theory, critical media studies, and recent literature on digital detox, social media addiction, phubbing, echo chambers, self-control, and digital well-being. The analysis applies qualitative content analysis, critical discourse analysis, and philosophical hermeneutics to reinterpret uzlah from a classical practice of withdrawal into a selective, conscious, and spiritually oriented strategy of digital self-restraint. The findings show that hyperconnectivity converts attention into an economic resource, intensifies dependence on notifications and social validation, and reduces the reflective space needed for self-awareness, moral judgment, and remembrance of God. Digital uzlah is therefore proposed as a practical framework consisting of temporary disconnection, digital spatial curation, and cognitive curation. These practices help users filter harmful content, resist algorithmic pressure, reclaim time, and restore inner dialogue. The study concludes that digital uzlah is not technological rejection, but an ethical discipline that enables Muslims to use digital media with awareness, self-control, truthfulness, and spiritual responsibility in the post-truth era. It contributes to communication studies by linking spirituality, media ethics, and resilience